Impact of Grounded Icebergs on the Hydrographic Conditions Near the Filchner Ice Shelf - Nøst, Ole Anders; Østerhus, Svein (Ocean, Ice, and Atmosphere: Interactions at the Antarctic Continental Margin, 1985)
Keywords: Sørishavet; Weddellhavet; havis; hydrografi; isberg; isfjell; isshelf; sjøis; vannmasser

Hydrographic and current measurements in the southern Weddell Sea 1979/80 - Gammelsrød, Tor; Slotsvik, Noralf (Polarforschung, 1981)
During the 1979-1980 expediton with the icebreaker Polarsirkel we had an excellent opportunity to study the physical oceanography of the inner part of the Weddell Sea. The ship followed the ice shelf barrier from Cape Norwegia at about 15 °W, and due to favourable ice conditions, it was able to penetrate all the way to the Antarctic Peninsula (60 0W). In this preliminary report we give a review of the physical oceanography programme which mostly consists of hydrographic (CTD) stations near the barrier, and also sorne current and water level measurernents. The different water masses observed are described and the possibility for a tidal-drlvcn upwelling near the ice shelf barrier is indicated.
Keywords: AABW; Sørishavet; Weddellhavet; bunnvannet; havis; hydrografi; isshelf; oseanografi; sjøis; sjøvann; vannmasser

Some satellite tracked iceberg drifts in the Antarctic - Vinje, Torgny E (Annals of Glaciology, 1980)
Keywords: Sørishavet; drivis; havis; isberg; isdrift; isfjell; oseanografi; sjøis; vannmasser